Study on organic substrate production by composting swine manure - WANG Kai-ying; ZHANG Yun; ZHU Xiao-lian (浙江大学学报. 农业与生命科学版)
Wood shavings, tea and herb residue are mixed with different mass percent of swine manure, namely 0, 20%, 30% and 40%, as contrasting groups of the composting experiment for production of organic substrates. Composting temperature, water content, pH electrical conductivity (EC), total carbon (TC), total nitrogen (TN), total phosphorus (TP) and overall porosity were measured. Results showed that 30% swine manure are most appropriate so far as the effect on composting temperature, composting duration and physical chemistry indexes of soilless planting substrate are considered.